MASA DEPAN UNI EROPA SETELAH KRISIS YUNANI - Triesanto Romulo Simanjuntak; Tunjung Wijanarka (Universitas Kristen Satya Wacana, 2016)
Crisis is a condition that show a state can’t ran the economic like usually. This condition appear with hardly the people to get access to living. The economic crisis can spread to other sector like politics, its can be call with multidimension crisis.European Union is a multilateral cooperation that the huge member is came from country in european continent. The beginning treaty is a European Coal and Steal Treaty within West European country, and now this treaty make an enlargment to all sector cooperation.The solution to this crisis will be shown from the cooperation between the member of European Union. Cooperation is an answer why the european state make a union, and cooperation is the answer how the member make a solution to solve this crisis.Keywords : Crisis, European Union, Cooperation